EFEKTIVITAS KOMUNIKASI PROGRAM PARTISIPASI MASYARAKAT OMBUDSMAN RI PROVINSI RIAU DALAM MENINGKATKAN PENGETAHUAN SAHABAT OMBUDSMAN MENGENAI MALADMINISTRASI - Vania Ramadhani; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In order to assess the effective communication in a public relations program, its main principles are needed, among others; credibility, context, content, clarity, continuity and consistency, channel, and capabilities or capabilities of the audience. One of the agencies implementing the program with the function of public relations is called the community participation program, activities carried out with the community called "Friends of the Ombudsman". This program was initiated to provide education which contains messages regarding matters relating to maladministration to the community through ombudsman friends. The purpose of this study was to determine how much the effectiveness of the communication program of the Ombudsman RI community participation program in Riau Province in increasing the ombudsman's knowledge about maladministration.This study uses quantitative research methods with descriptive types, the data in this study were obtained by data collection techniques, namely through direct distribution of questionnaires to the people who participated in the Riau Province Ombudsman Community Participation program (ombudsman friends) with a total sample of 80 respondents. calculated using census sampling technique. The data obtained in this study were analyzed using descriptive statistics.Based on the results of this study, obtained an average of 3.41 for the seven indicators of communication effectiveness used. This shows that communication in the Riau Province Ombudsman RI community participation program is very effective in increasing the ombudsman's knowledge about maladministration. The indicator with the highest average score is the credibility indicator, which shows that the ability of the presenters in the program is trusted and respected by the audience for their competence. The results which state that the program is very effective in increasing the knowledge of ombudsman friends who are reviewed through indicators measuring an effectiveness in the program is different from the data which states that the community's low knowledge of maladministration, therefore it is necessary to review the program being implemented in order to achieve the target. wider so as to increase public knowledge about maladministration in society in general.                                       Keywords: Effectiveness Communication, Knowledge, Maladministration